A biopsy technique to predict quality in the live beef animal with emphasis on tenderness - Michael E. Dikeman; C.C. Melton; H.J. Tuma; G.R. Beecher (Kansas Agricultural Experiment Station Research Reports, 1970)
Because tenderness is considered the most desired eating characteristic in meat, more emphasis should be placed on this trait in evaluating beef quality in breeding and selection programs. Both tenderness and marbling are highly heritable traits (Heritability = approximately 0.6), therefore much improvement could be made through progeny testing of sires; however, this requires considerable time and expense. This consideration, plus an increasing interest in feeding young beef bulls for market, led to an interest in applying a biopsy technique to evaluate and predict meat quality in the live animal.
Keywords: Cattlemen' s Day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station); 536; Beef; Tenderness; Quality; Marbling